Communication Planning of Education Council Managers in Increasing the Quality of Religious Education in The Digital Era in Aceh Tamiang District - Azhar Azhar; Syukur Kholil; Soiman Soiman (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Communication planning plays a crucial role in supporting education board members in improving the quality of religious education in the digital era. The use of technology and digital platforms is effective in overcoming study time restrictions and increasing students' understanding and skills in implementing Islamic law. This study aims to reveal the communication planning of education council administrators in advancing the quality of digital-era religious education in Aceh Tamiang District through a qualitative approach using the phenomenological method. The results concluded that the planning involved six steps: field mapping, communication planning, a program to improve the quality of religious education, strategies, activities, and targets and objectives. Its realization takes two forms, namely the implementation of the communication plan and the dissemination of the plan. Obstacles to program implementation included the lack of optimal local content curriculum, but support for the qanun on the Regional Education Council and the Regulations of the Aceh Tamiang Regent, as well as collaboration with teachers, principals, school supervisors, and other institutions, were significant supports. The whole of this research shows that communication planning has structured stages to improve the quality of religious education in the digital era by recognizing variations in realization and the important role of inhibiting and supporting factors.